PSYCHOEDUCATIONAL MENTORING FOR ADOLESCENTS TO PREVENT SEXUAL VIOLENCE, BULLYING, AND STRENGTHEN MENTAL HEALTH IN GUNUNGANYAR, SURABAYA - Arista Pratama; Ika Korika Swasti; Nalini Muhdi; Nanang Haryono; Endang Sholihatin; Anggita Faradila; Ailsa Belinda Leilani (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
This community service program was implemented under the UPN Veteran Jawa Timur Mengabdi scheme in Gunung Anyar Subdistrict, Surabaya. The primary objective was to enhance adolescents’ capacity to prevent sexual violence and bullying, while simultaneously strengthening their mental health literacy. The program employed a participatory psychoeducational approach, incorporating interactive lectures, group discussions, role-play simulations, and training on the use of the Circle of 6 digital application as a preventive tool. A total of 15 adolescents from the local Karang Taruna youth organization participated in a training session held on June 12, 2025, followed by mentoring sessions on August 6 and 14, 2025. Evaluation using pre- and post-test instruments indicated a 71% improvement in participants’ knowledge and skills, particularly in recognizing the forms and impacts of sexual violence and bullying, developing assertive communication, and building readiness to act as bystanders in high-risk situations. The use of the Circle of 6 application was proven effective in enhancing digital literacy and emergency preparedness among participants. Furthermore, the psychoeducational approach significantly increased participants’ awareness of stress, anxiety, and depression symptoms and encouraged a willingness to seek professional help. The novelty of this program lies in the integration of psychoeducational methods, digital technology, and community participation, which collectively empower adolescents to become agents of change within their social environment. Despite challenges such as limited training duration and varying levels of participant engagement, the program demonstrated strong potential for replication and scalability through cross-sector collaboration. Overall, this initiative contributes to the development of community-based intervention models grounded in science and technology (IPTEKS) to support efforts in preventing violence and promoting adolescent mental health in Indonesia.